1992
DOI: 10.1016/0014-5793(92)80034-e
|View full text |Cite
|
Sign up to set email alerts
|

The 93 kDa protein gephyrin and tubulin associated with the inhibitory glycine receptor are phosphorylated by an endogenous protein kinase

Abstract: The 93 kDa protein gephyrin is a tubulin binding peripheral mcmbranc protein that is associated with the inhibitory glycinc receptor and has been implicated in its anchoring at central synapses. Here, we demonstrate that gephyrin as well as co-purifying tubulin are phosphorylated by a kinase aclivity which is cndogenous to highly purified glycine receptor preparations. This kinase phosphorylates scrine and threonine residues and utilizes ATP, but not GTP, as phosphate donor. Its activity is not affected by var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Presently, mutants of the trimer interface, which would generate monomeric gephyrin or E. coli MogA, are not available to test the role of oligomerization for enzymatic function. However, oligomerization of native gephyrin has been observed previously in sedimentation studies (45) and suggested to play a role in the clustering of inhibitory receptors at developing postsynaptic membrane specializations (15).…”
Section: Discussionmentioning
confidence: 76%
“…Presently, mutants of the trimer interface, which would generate monomeric gephyrin or E. coli MogA, are not available to test the role of oligomerization for enzymatic function. However, oligomerization of native gephyrin has been observed previously in sedimentation studies (45) and suggested to play a role in the clustering of inhibitory receptors at developing postsynaptic membrane specializations (15).…”
Section: Discussionmentioning
confidence: 76%
“…However, gephyrin has been identified as a phosphoprotein when copurified with the GlyR (which has kinase activity), 40 and mass spectrometric analyses of rat and mouse brains revealed that gephyrin has 22 phosphorylation sites, most of which are located within the C domain (except for threonine 324, which lies in the E domain 25,[41][42][43] ) (Figure 1). These modifications might induce conformational changes by affecting the structure of the C domain or the neighboring G and E domains, thereby altering the clustering, trafficking and binding properties of gephyrin.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…Earlier studies reported that gephyrin in GlyR preparations from rat spinal cord is phosphorylated (22). Therefore, we used phosphatase treatment to remove all phosphates from gephyrin and compared the binding of mAb7a and Ab-175 antibodies in immunoblots.…”
Section: Cb Knockdown Abolishes the Formation Of Gephyrin Clusters Inmentioning
confidence: 99%
“…Phosphorylation of gephyrin was first reported in 1992 (22). More recently, the binding of gephyrin to the peptidyl-prolyl cis/trans-isomerase Pin1 was analyzed and allowed the identification of amino acid residues (Ser-188, in the C-domain as major determinants of phosphorylation dependent Pin1 binding and also of gephyrin clustering (23).…”
mentioning
confidence: 99%